Probing Electric Field in an Enclosed Field Mapper for Characterizing Metamaterials - Sucheng Li; Chendong Gu; Yadong Xu; Shahzad Anwar; Weixin Lu; Zhi Hong Hang; Bo Hou; Huanyang Chen (International Journal of Antennas and Propagation)
Spatially mapping electromagnetic fields in the quasi-two-dimensional field mapper (a parallel plate waveguiding system; Justice et al. (2006)) for characterizing metamaterial devices, especially those integrating the metal boundary, may encounter troubles including electromagnetic leakage caused by the air gap and energy guiding along finitely high metal walls. To eradicate them, a moving contact approach is proposed. The physical air gap between the mobile metal walls and the stationary upper plate of the mapper is closed, while their relative movement is still allowed during the field mapping. We demonstrate the method of closing the gap by mapping the E-field distribution in a rectangular waveguide.